Pendidikan Kesehatan Tentang Kondisi Sanitasi Lingkungan dan Pemberantasan Sarang Nyamuk (PSN) di Panti Asuhan Asrama Sahabat Yatim Pekanbaru - Donny Hendra; Anugrah Pralingga; Yessi Azwar; Siska Mulyani; Maswir Maswir; Noviyanti Noviyanti (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Sanitation is part of environmental health science which includes the methods and efforts of individuals or communities to control and manage the external environment which is dangerous to health and which can threaten human survival. Meanwhile, basic sanitation is the minimum sanitation required to provide a healthy environment that meets health requirements which focuses on monitoring various environmental factors that influence human health. Basic sanitation efforts include providing clean water, disposal of human waste (latrines), waste management (trash cans) and waste water disposal channels (SPAL). Through a preliminary survey conducted at the Sahabat Yatim Dormitory Orphanage and from interviews conducted by the community service team, it was discovered that several children at the Sahabat Yatim Dormitory orphanage had a fairly high history of dengue fever sufferers and there were still many conditions in the orphanage that did not meet health requirements. Thus, there is still the possibility of problems related to environmental sanitation and eradicating mosquito nests (PSN) at the Pekanbaru Orphanage Friends Dormitory orphanage. The aim of this activity is to increase the knowledge of children in orphanages about environmental sanitation and eradicating mosquito nests.This community service was carried out at the Sahabat Yatim Dormitory Orphanage on June 29 2022. The method used was health education through group counseling. The result of this community service is to increase the knowledge of children in foster care about environmental sanitation and making compost.